2020
DOI: 10.1093/braincomms/fcaa132
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease promotes tau pathology in Alzheimer’s disease

Abstract: Small vessel cerebrovascular disease, visualized as white matter hyperintensities on T2-weighted MRI, contributes to the clinical presentation of Alzheimer’s disease. However, the extent to which cerebrovascular disease represents an independent pathognomonic feature of Alzheimer's disease or directly promotes Alzheimer’s pathology is unclear. The purpose of this study was to examine the association between white matter hyperintensities and plasma levels of tau and to determine if white matter hyperintensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 69 publications
(75 reference statements)
6
67
3
Order By: Relevance
“…No changes were detected regarding Aβ pathology. Similar observations were done in AD patients, in which cerebral hypoperfusion appeared to have a causative link with tau pathology but not Aβ pathology [47,48]. Intriguingly, brain aging is also marked by hypoperfusion due to the decrease in cerebral blood flow and the loss of BBB integrity [12][13][14], which may lead to deficits in nutrient import, including glucose, into the brain.…”
Section: Age-related Bioenergetic Impairments In the Brain: A Trigger For Tau Pathology?supporting
confidence: 69%
See 1 more Smart Citation
“…No changes were detected regarding Aβ pathology. Similar observations were done in AD patients, in which cerebral hypoperfusion appeared to have a causative link with tau pathology but not Aβ pathology [47,48]. Intriguingly, brain aging is also marked by hypoperfusion due to the decrease in cerebral blood flow and the loss of BBB integrity [12][13][14], which may lead to deficits in nutrient import, including glucose, into the brain.…”
Section: Age-related Bioenergetic Impairments In the Brain: A Trigger For Tau Pathology?supporting
confidence: 69%
“…Evidence has been linking disturbances in brain metabolism and tau pathology. For instance, studies have shown that cerebral hypoperfusion, which impairs brain energy metabolism, leads to an increase in tau abnormal phosphorylation in different animal models [45][46][47]. In the 3xTgAD model of AD, cerebral hypoperfusion (caused by unilateral common carotid artery occlusion) induced a significant increase in tau phosphorylation in the hippocampus of 3-month-old animals compared to controls (sham-operated mice) [45].…”
Section: Age-related Bioenergetic Impairments In the Brain: A Trigger For Tau Pathology?mentioning
confidence: 99%
“…Brain amyloid burden and the interaction between plasma tau and white matter of hyperintensity could distinguish AD and MCI patients from controls, with accuracies as 77.6% and 63.3%, respectively. Moreover, increased tau levels in plasma and CSF and hyperphosphorylated tau level in the ipsilateral hippocampus and cerebral hemisphere were observed in aged mice subjected to transient focal cerebral ischemia [ 68 ]. All these findings suggested cerebrovascular dysfunctions could induce and promote tau pathology in AD.…”
Section: Interplays Between Ad Pathologies and Cerebrovascular Alterationsmentioning
confidence: 99%
“…Moreover, EOD is a good model to study the factors interacting with both dementia and the aging process, such as the vascular factor, whose contribution is often questioned in the dementia pathogenesis since the vessels are also undergoing degeneration during the aging process. Recent reports (Zlokovic, 2011;Laing et al, 2020) have shown that microvascular influences affecting cerebral microcirculation may contribute to the pathogenesis of dementia. Reports have also suggested that decreased cerebral blood flow occurs before the onset of clinical dementia which was trailed by decreased amyloid-beta clearance resulting in neurotoxicity (Kalaria et al, 2012; making the possibility of vascular factor as a pre-clinical dementia biomarker.…”
Section: Introductionmentioning
confidence: 99%